Synthesis of a novel cobalt (III) 1,2-naphthalocyanine complex with mixed axial ligands - Yu, Derrick Ethelbert C. (Animo Repository, 2002)
Evidence for the synthesis of u-cyano(1,2-naphthalocyaninato)cobalt(III) (compound 3), a novel macrocyclic transition metal complex which are linked by linear bridging cyano ligands containing delocalizable pi-eletrons capable of forming polymeric stacked arrangements, via splitting off potassium cyanide from potassium dicyano(1,2-naphthalocyaninato)cobalt(III) (compound 2), is presented. Treatment of compound 3 with pyridine leads to a monomeric complex of cobalt(III) 1,2-naphthalocyanine complex with mixed axial ligands, a novel cyano(1,2-naphthalocyaninato)cobalt(III) pyridine adduct (compound 4). Compounds are characterized by IR, UV-VIS, SEM, and mass spectroscopy.